Factors influencing dividend payout decisions: Evidence from South Africa - Lovemore Nyere; Nicolene Wesson (South African Journal of Business Management, 2019)
Background: Dividend payout is one of the most debated contemporary corporate finance Issues. No universal theoretical model describes the factors that corporate managers consider in dividend payout decisions. This study extends previous South African empirical research on dividend payout trends and motivations for Johannesburg Stock Exchange (JSE)-listed industrial companies over the period 1999–2014. The study period coincides with the introduction of share repurchases as an alternative distribution method, covers multiple dividend distribution regulatory amendments and overlaps the global financial crisis of 2008.Objectives: The aim of this study was to ascertain whether the global financial crisis of 2008 affected dividend payouts and to identify factors that influenced dividend payout decisions of JSE-listed industrial companies over the period 1999–2014.Method: Descriptive statistics and a fixed-effects panel regression analysis were applied to dividend data extracted from published annual reports of JSE-listed industrial companies over the period 1999–2014.Results: Dividend distributions of JSE-listed industrial companies increased over the study period in contrast to declining global dividend distribution trends. A significant increase in dividend payout was found when comparing pre- and post-recession periods, in line with the positive impact of dividend distribution regulatory reforms. Company size (+), profitability (+), sales growth (-) and free cash flow (-) were identified as significant factors that influence dividend distributions of JSE-listed industrial companies.
Keywords: 650